2020
DOI: 10.3390/joitmc6030086
|View full text |Cite
|
Sign up to set email alerts
|

What Do Chinese Entrepreneurs Think about Entrepreneurship: A Case Study of Popular Essays on Zhisland

Abstract: Entrepreneurship is becoming increasingly essential in this current era of the knowledge economy. It contributes to the innovation of products and services as well as improved processes. In the long-run, it can also improve the sustainability of the economy by depicting better efficiency and social goals. To stimulate entrepreneurship, it is essential to investigate the thinking behind entrepreneurship or what entrepreneurs think about entrepreneurship. Such investigations should encompass the mental images of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Authors [8] reviewed current research and found that 'the concept of entrepreneurship has evolved from launching a new business to any entrepreneurial activities that involve a new way to operate a business or NGO, or an existing organization'. The need for intrapreneurial traits and behaviors extends to many areas of organizations and has become a strategic issue for ensuring the performance of organizations [9] as employees need to adopt intrapreneurial roles, such as innovators and differentiators [10].…”
Section: Introductionmentioning
confidence: 99%
“…Authors [8] reviewed current research and found that 'the concept of entrepreneurship has evolved from launching a new business to any entrepreneurial activities that involve a new way to operate a business or NGO, or an existing organization'. The need for intrapreneurial traits and behaviors extends to many areas of organizations and has become a strategic issue for ensuring the performance of organizations [9] as employees need to adopt intrapreneurial roles, such as innovators and differentiators [10].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Q-Methodology can also be integrated in the value chain of other methodologies. Some applicable cases would include generating the input set for system dynamics analysis such as the those performed in entrepreneurship assessment [46] or the complementation of strictly indicator-based works [47,48]. For the later type of research, the opinion of policy makers and R&D agents would allow visualizing not only what is strictly bound to indicators but also the feeling of the open innovation community.…”
Section: Applicability Of Q Research Methods To Open Innovation Researchmentioning
confidence: 99%
“…As various actors are involved in the PLM system over time [39][40][41], the system dynamic model of PLM includes all needed characteristics (multi-scales, capacity for showing different relationships and feedbacks, strategic planning) [34,35] to utilize various methods towards providing aspects of product lifecycle management [77]. Product lifecycle management systems allow firms to integrate all of the business processes and information related to products portfolio at every managerial and technical organizational level [77,78].…”
Section: System Dynamic Model Of Plm and Open Innovationmentioning
confidence: 99%
“…Many studies used the system dynamic modeling to show the different relationships between variables. It has been used to model the different relationships and feedback between the variables in a specific system over time [34] and to analyze the system behavior such as a company, guiding policymakers to manage companies better [35]. The SD approach has been widely used in recent years to solve problems in different healthcare fields, such as supply chain management, healthcare policy, technology and information, aging, and population [36].…”
Section: Introductionmentioning
confidence: 99%